Influence of Exposure at Different Altitudes on the Executive Function of Plateau Soldiers—Evidence From ERPs and Neural Oscillations - Wei, Xin; Ni, Xiaoli; Zhao, Shanguang; Chi, Aiping (Frontiers in Physiology, 2021)
This study investigates the changes in soldiers' brain executive function at different altitude environments and their relationship with blood oxygen saturation. Stratified sampling was conducted in different altitude 133 active-duty soldiers who were stationed in Weinan (347 m, n = 34), Nyingchi (2,950 m, n = 32), Lhasa (3,860 m, n = 33), and Nagqu (4,890 m, n = 34) for 2 years. The Go/NoGo paradigm with event-related potentials (ERPs) and event-related oscillations (EROs) was used to explore the time and neural oscillation courses of response inhibition. Behavioral results revealed that at the 4,890-m altitude area, the soldiers had the highest false alarm rate, the longest reaction time, and the slowest information transmission rate. The electrophysiological results revealed that NoGo-N2 and N2d decreased with increasing altitude, with significant changes at 3,860 m; the amplitudes of NoGo-P3 and P3d in plateau groups were significantly more negative than the plain and changed significantly at 2,950 m. The results of correlation analysis showed that NoGo-P3 was negatively correlated with altitude (r = −0.358, p = 0.000), positively correlated with SpO2 (r = 0.197, p = 0.041) and information translation rate (ITR) (r = 0.202, p = 0.036). P3d was negatively correlated with altitude (r = −0.276, p = 0.004) and positively correlated with ITR (r = 0.228, p = 0.018). N2d was negatively correlated with ITR (r = 0.204, p = 0.034). The power spectrum analysis of NoGo-N2 and NoGo-P3 showed that the power of δ and θ bands at the plateau area was significantly lower than the plain area and showed a significant step-by-step decrease; the α-band power increases significantly only in the area of 4,890 m. The effect of chronic hypoxia exposure at different altitudes of the plateau on the response inhibition of soldiers was manifested: 3,860 m was the altitude at which the brain response inhibition function decreased during the conflict monitoring stage, and 2,950 m was the altitude at which it dropped during the response inhibition stage. In addition, the soldier's brain's executive function was closely related to SpO2, and a reduction in SpO2 may lead to a decline in response inhibition.